AN OVERVIEW OF CLOUD TESTING AS A SERVICE - Parmar, Amandeep Kaur; Singh, Navjeet; Singh, Dr. Gurdev (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Testing is an important process for software quality assurance. A cloud infrastructure creates significant new opportunities for software quality assurance and testing. Making the test infrastructure that directly represents the production cloud infrastructure is too expensive – in terms of hardware, software licenses and testing professionals. To deal with this challenge the paper gives an overview of various cloud testing strategies and also introduces ‘Testing as a Service’, using Cloud computing.